The Oxford companion to wine - Jancis Robinson (Oxford University Press, 2006)
The Oxford Companion to Wine offers almost 4,000 entries on every wine-related topic imaginable, from regions and grape varieties to the owners, connoisseurs, growers, and tasters in wine through the ages; from viticulture and oenology to the history of wine. Tracing the consumption and production from the ancient world to the present day, the Companion is a remarkable resource for gaining further appreciation for a beverage whose popularity has only increased with time